Propofol requirement for insertion of I-gel versus laryngeal mask airway: A comparative dose finding study using Dixon's up-and-down method - Aparna Ashay Nerurkar; Wasim Shaikh; Bharati Anil Tendolkar (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: Propofol is the drug of choice when used as sole anesthetic agent for placement of supraglottic airway devices. We aimed to find and compare the propofol dose required for smooth first attempt insertion of I-gel versus the classic laryngeal mask airway (cLMA) using Dixon's up-and-down method. Material and Methods: Prospective randomized controlled trial (n-60) was planned. I-gel or cLMA was inserted 60 s after propofol injection whose dose was calculated based on previous patients response as per Dixon's up-and-down method. Propofol requirements for successful placement of devices was noted and compared. Difference between the groups was measured by ANOVA. A P < 0.05 was considered as statistically significant. Results: Significantly lower (P < 0.001) propofol dose was required for I-gel (2.02 ± 0.26 mg/kg) insertion than cLMA (2.70 ± 0.28 mg/kg). Conclusions: I-gel requires significantly lower dose of propofol for insertion when compared to cLMA.